Good Service Strategies Affect Competitive Advantage - Desfitrina Desfitrina; Zulfadhli Zulfadhli; Widarti Widarti (International Review of Management and Marketing, 2019)
The purpose of this study is to determine the effect of service on competitive advantage. The unit of analysis in this study is the manager of a manufacturing industry company in South Sumatra. The results showed that a good level of service would create a competitive advantage that had the characteristics possessed by managers to produce a production advantage over similar companies. Furthermore it was found that the effect of service on competitive advantage companies must understand how to manage the various resources they have. An important key to winning competition lies in the company's ability to create competitive advantage. Competitive advantage can come from various company activities such as in designing, producing, marketing, delivering, and supporting its products. Each of these activities must be directed to support a relatively low cost position with good quality on the basis of creating differentiation.